Analysis of Changes in United States Foreign Policy the Era of the Barack Obama Government - Nurtina, Sitti (The Easta Journal Law and Human Rights, 2024)
This article explains the foreign policy of the Republic of the United States in the Asia Pacific region which is studied through analysis of epistemological, ontological and axiological aspects. This article tries to look at the reasons for the United States changing the focus of its foreign policy from the Middle East to the Asia Pacific Region. In the regional dynamics that occur, China plays an important role along with increasing its national capabilities. In this regard, this article will discuss and provide an explanation of the foreign policy created by America, namely the Asian Pivot, using an analytical framework based on the Balance of Threat theory with the application of the United States' offshore balancing strategy to the Asia-Pacific region. In addition, this article analyzes funnel causality, namely the sources that form the basis of United States policy making in the Asia Pacific. The United States is a very unique country in terms of its political system both at home and abroad, its foreign policy is able to influence the world political landscape. This research is qualitative in nature using a textual study method by analyzing secondary data from various related literature. The results of the literature study show that changes in the focus of American foreign policy were due to factorsChina's increasing national capabilities are seen as a challenge to United States national interests.